Hearing difficulties, ear-related diagnoses and sickness absence or disability pension - a systematic literature review - Friberg Emilie; Gustafsson Klas; Alexanderson Kristina (BMC, 2012)
Abstract Background Hearing difficulties is a large public health problem, prognosticated to be the ninth leading burden of disease in 2030, and may also involve large consequences for work capacity. However, research regarding sickness absence and disability pension in relation to hearing difficulties is scarce. The aim was to gain knowledge about hearing difficulties or other ear-related diagnoses and sickness absence and disability pension through conducting a systematic literature review of published studies. Methods Studies presenting empirical data on hearing difficulties or ear-related diagnoses and sick leave or disability pension, published in scientific peer-reviewed journals, were included. Studies were sought for in three ways: in literature databases (Pub-Med, Embase, PsycInfo, SSCI, and Cochrane) through March 2011, through scrutinising lists of references, and through contacts. Identified publications were assessed for relevance and data was extracted from the studies deemed relevant. Results A total of 18 studies were assessed as relevant and included in this review, regardless of scientific quality. Fourteen studies presented empirical data on hearing difficulties/ear diagnoses and sick leave and six on these conditions and disability pension. Only two studies presented rate ratios or odds ratios regarding associations between hearing difficulties and sick leave, and only two on hearing difficulties and risk of disability pension. Both measures of hearing difficulties and of sick leave varied considerable between the studies. Conclusions Remarkably few studies on hearing difficulties in relation to sickness absence or disability pension were identified. The results presented in them cannot provide evidence for direction or magnitude of potential associations.